2010
DOI: 10.1016/j.ijgo.2010.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Cervical priming with misoprostol before manual vacuum aspiration versus electric vacuum aspiration for first‐trimester surgical abortion

Abstract: CTRI/2009/091/000008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Cervical priming with vaginal misoprostol before MVA has shown to significantly reduce the need for cervical dilation and improve the efficacy of the procedure [19]. For many of the elective patients in the study, the use of misoprostol alone before procedure was enough to ensure that the cervix was dilated, allowing safer evacuation by minimising cervical trauma related to instrumental dilation and reducing the discomfort of cervical dilation.…”
Section: Discussionmentioning
confidence: 97%
“…Cervical priming with vaginal misoprostol before MVA has shown to significantly reduce the need for cervical dilation and improve the efficacy of the procedure [19]. For many of the elective patients in the study, the use of misoprostol alone before procedure was enough to ensure that the cervix was dilated, allowing safer evacuation by minimising cervical trauma related to instrumental dilation and reducing the discomfort of cervical dilation.…”
Section: Discussionmentioning
confidence: 97%
“…In general, differences between misoprostol and placebo in terms of operative time and blood loss are statistically, but not clinically, significant. The effectiveness of misoprostol is not influenced by whether manual vacuum aspiration or electric suction is used [140].…”
Section: Is Misoprostol Safe and Effective For Cervical Priming In Thmentioning
confidence: 96%
“…Several randomized trials have compared misoprostol and placebo or no therapy for cervical priming before firsttrimester surgical abortion and found that misoprostol increases baseline dilation and facilitates further dilation. These studies analyzed vaginal doses of 100 to 750 mcg [19,61,91,95,96,101,103,105,139,140], oral doses of 400 to 600 mcg [103,104,141] and a sublingual dose of 400 mcg [107,113,142]. Almost all of these studies demonstrated an increased baseline cervical dilatation with misoprostol, and some also found a greater subjective ease of dilation [19,95,104,[140][141][142], lower measured cumulative force with dilation [61,103], shorter procedure time [19,91,95,96,104,107,113] or lower estimated blood loss [103,104,107,113].…”
Section: Is Misoprostol Safe and Effective For Cervical Priming In Thmentioning
confidence: 99%
“…However, they were similar in the incidence of sepsis post procedure, uterine perforation, or the need for re-evacuation [21]. MVA and EVA do not appear to differ substantially in efficacy [22]. VA can be performed in the absence of a fully equipped facility and at secondary health facilities, with or without electricity, and without the capacity for general anesthesia.…”
Section: Vacuum Aspiration (Va)mentioning
confidence: 96%
“…VA can be performed in the absence of a fully equipped facility and at secondary health facilities, with or without electricity, and without the capacity for general anesthesia. It is suitable for low-income settings because it is more accessible and reduces the consequences of blood loss and worsening infection associated with transportation to tertiary health facilities [22].…”
Section: Vacuum Aspiration (Va)mentioning
confidence: 99%